Market or Government: Lessons from a Comparative Analysis of the Experience of Pakistan and India (The Distinguishedl Lecture) (The Pakistan Development Review, 1991)
In the 1980s a remarkable consensus developed that all economies, including the Less Developed Countries (LDC), will achieve both more rapid growth and alleviation of poverty with greater reliance on a market oriented strategy and minimal government direct control and ownership in the economy. The disputes that remain have to do with marginal issues: how fast to move from dirigiste to private enterprise systems and the extent to which there is a residual role for government in dealing with market imperfections. There remain a few unregenerate interventionists, especially in South Asia, but they are definitely a beleaguered minority. Even more remarkable is that the consensus is not only with respect to the economic efficiency of the market, but is nearly as great on its effectiveness in reducing poverty. A powerful tool for analyzing whether greater reliance on markets indeed is successful in raising the rate of growth and reducing the extent of poverty is to compare the experience of similar countries with different strategies in that respect A comparison of the experience of India with that of Pakistan and Bangladesh during the last 40 years can be particularly fruitful because: